Capacity Building in Humanitarian Action in the Global South. An analysis of the priority needs of organisations through a stady carried out in the Republic of Cabo Verde (Research, Society and Development, 2025)
The article aimed to identify priority training needs in relation to the capacities of institutional responses (public and private) operating in the field of humanitarian action in Cabo Verde. A qualitative methodology was used in a descriptive and exploratory approach, using six semi-structured interviews with the heads of these institutions. This study offers an in-depth analysis of the main training demands, evaluating the response capacities and experiences of those responsible and leaders of state and municipal institutions and civil society organizations that operate with humanitarian action, in the Cape Verdean context. The results identified priority areas such as: the humanitarian programme cycle; the areas of intervention in Humanitarian Action; and the ecosystemic impact of climate change. The data obtained points to a need to create high-level training programmes that provide the acquisition of technical and reflective skills in humanitarian response based on the local context.